STRUKTUR GENETIK Calliandra calothyrsus DI INDONESIA MENGGUNAKAN PENANDA RANDOM AMPLIFIED POLYMORPHISM DNA (RAPD) - ILG Nurtjahjaningsih; Purnamila Sulistyawati; Anto Rimbawanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2016)
Calliandra calothyrsus was introduced to Indonesia from Guatemala in 1930s and had been planted widely throughout Indonesia for fuel wood. Genetic diversity within and among population is an important factor for initiating breeding program. Aim in this study was to evaluate genetic structure of C. calothyrsus in Indonesia, to obtain a better understanding of the history of the distribution and efficiency of breeding strategy of this species. Leaf samples were collected in a seedling seed orchard plot from 10 populations. Six RAPD markers consisted of 34 loci were used to analyze genetic diversity and genetic structure. The results showed that genetic diversity was in low to moderate level (mean HE= 0.321). The AMOVA analysis showed that genetic differentiation among geographical sources was significant, also among populations within geographical sources and among individual within populations as well. It was revealed that the 10 populations originated from only two ancestors. The limited number of ancestors resulted low to moderate genetic distances among populations (mean Da=0.070). In conclusion, C. calothyrsus has moderate genetic diversity within population and weak genetic structure among populations. Genetic diversity in population/individual level should be considered as a selection unit in the breeding strategies.